Tixagevimab/cilgavimab for the prevention of COVID-19 in vaccine-refractory patients with autoimmune diseases: a prospective cohort study. - Minopoulou, Ioanna; Tascilar, Koray; Corte, Giulia; Mutlu, Melek Yalcin; Schmidt, Katja; Bohr, Daniela; Hartmann, Fabian; Manger, Karin; Manger, Bernhard; Korn, Klaus; Kleyer, Arnd; Simon, David; et al. (Rheumatology, 2024)
OBJECTIVES: To investigate the effects of passive immunization with the anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) monoclonal antibodies tixagevimab/cilgavimab on humoral responses and on coronavirus disease 2019 (COVID-19) outcomes in vaccine-refractory patients with immune-mediated inflammatory diseases (IMIDs) at high risk of severe COVID-19. METHODS: A prospective cohort study was performed on a cohort of high-risk vaccine-refractory IMID patients treated with a single dose of tixagevimab/cilgavimab (150 mg/150 mg). COVID-19 outcomes as well as serum and salivary anti-SARS-CoV-2 IgG were assessed at baseline and for at least 6 months. Results were compared with an untreated high-risk vaccine-refractory IMID population. Standardized incidence ratios (SIRs) of COVID-19 compared with the general population were calculated for both groups. RESULTS: A total of 38 high-risk IMID patients received tixagevimab/cilgavimab and were compared with 114 untreated high-risk IMID controls. Serum anti-spike IgG increased to 6.6 OD (s.d. 0.8) at day 1 and remained positive up to month 6 [6.3 OD (s.d. 1.4)]. Salivary anti-spike IgG peaked at month 2 [1.6 OD (s.d. 1.1)] and decreased from month 3 [0.8 OD (s.d. 0.3)]. No severe or extended infection was observed in the tixagevimab/cilgavimab group. Compared with the general population, the SIR of COVID-19 in treated patients was 0.76 (95% CI 0.24, 1.58) despite the increased risk profile. The SIR of the control group was 1.51 (95% CI 1.07, 2.02), corresponding to a significantly increased incidence. CONCLUSIONS: Passive immunization with tixagevimab/cilgavimab is safe and effective in inducing anti-SARS-CoV-2 immunity and potentially in preventing COVID-19 in high-risk vaccine-refractory IMID patients. These data provide a proof of concept for the use of monoclonal antibodies as a preventative strategy against SARS-CoV-2 in vulnerable populations.
EVALuna2:540332